2021
DOI: 10.3389/fgene.2021.705803
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Reveals Human-Mediated Introgression From European Commercial Pigs to Henan Indigenous Pigs

Abstract: Introgression of genetic features from European pigs into Chinese pigs was reported possibly contributing to improvements in productivity traits, such as feed conversion efficiency and body size. However, the genomic differences from European pigs and the potential role of introgression in Henan indigenous pigs remains unclear. In this study, we found significant introgression from European pigs into the genome of Chinese indigenous pigs, especially in Henan indigenous pigs. The introgression in Henan indigeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This has led to an update in the genetic resources of Chinese domestic pigs. Previous studies have found genetic components from EP in Chinese breeds, [ 11 , 14 16 , 40 , 41 ], but EP introgression into LJP (a specific Chinese pig populations) has not been studied. Our study confirms the presence of EP introgression into multiple Chinese pig populations, including NCDP, SWCDP, TIBP-E, and LJP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to an update in the genetic resources of Chinese domestic pigs. Previous studies have found genetic components from EP in Chinese breeds, [ 11 , 14 16 , 40 , 41 ], but EP introgression into LJP (a specific Chinese pig populations) has not been studied. Our study confirms the presence of EP introgression into multiple Chinese pig populations, including NCDP, SWCDP, TIBP-E, and LJP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has documented three distinct waves of introgression from Europe to Asia over the past 200 years [ 13 ]. In addition, EP introgression may have induced phenotypic changes in indigenous Chinese pigs, such as introgression of the European NR6A1 haplotype, which can increase the number of vertebrae, body size, and feed-conversion efficiency [ 14 , 15 ] and of the KIT alleles from the Large White (LW) breed into the Pudong white pig, which has resulted in expression of the white coat colour phenotype [ 16 ]. Furthermore, transmission of EP-introgressed segments among Chinese pig populations may also have occurred in China in recent decades [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence support this: During the Industrial Revolution, the presence of shared haplotypes between Meishan and Duroc pig breeds further supported the notion of Asian-derived introgression and the specific contribution of Meishan pigs to increasing sow fertility in European pigs [7,[13][14][15]; the detection of more than a quarter of the genetic components of European commercial pigs in current Laiwu pig populations indicates large-scale interspecific crosses and gene introgression; these processes have been instrumental in incorporating genetic material from European breeds and improving important economic traits in Laiwu pigs [16]. These findings collectively emphasize the role of selection and genetic admixture in pig breeding, showcasing how intentional hybridization and introgression can lead to the enhancement of desired traits and improvements in economic performance in pig populations [7,9,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 94%
“…It serves as the raw material upon which the genetic variation within a species is built [ 1 , 2 , 3 , 4 ]. Both naturally occurring and artificially mediated genetic introgressions among pig breeds/populations have the potential to significantly impact and reshape a wide range of phenotypes [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The Large White pig breed is renowned for its prolificacy, meat quality, and adaptability to various environments.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, using genomic SNP array data of core population of native Henan pig breeds, we found that native Henan pig breeds have a common lineage with some representative northern and eastern Chinese pig breeds (Bamei, Min, Laiwu, and Erhualian). We also detected the introgression of foreign genes on native Henan pig breeds (under review; Qiao et al, 2019; Wang et al, 2021) using DNA deep sequencing data and reduced‐representation genome sequencing data of random selected individuals of native Henan pig breeds.…”
Section: Introductionmentioning
confidence: 99%